“Developing Creative Thinking in Visual Arts Lessons for Grades 5–7 through Project-Based Learning” - Axmedov Dilmurod Xolmamatovich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract:This article explores the pedagogical and methodological aspects of using project-based learning to develop creative thinking and skills in grades 5–7 students during visual arts lessons. The study shows that project-based methods enhance students’ independent work, foster problem-solving abilities, and stimulate creative decision-making. The integration of interactive projects and collaborative activities makes lessons more engaging, supports artistic literacy, and encourages active participation.